Analysis and optimization of the wall-climbing robot with an adsorption system and adhesive belts. (27th May 2020) - Liu, Jinfu; Xu, Linsen; Xu, Jiajun; Liu, Lei; Cheng, Gaoxin; Chen, Shouqi; Xu, Hong; Shi, Jia; Liang, Xingcan
This article presents an innovative wall-climbing robot for detection on smooth wall surfaces, which consists of a vacuum adsorption system and adhesion belts, making the robot flexible and effectively steerable. Moreover, the detailed attachment mechanism is further analyzed for the climbing tasks. Safe operating conditions, kinematics, and dynamic model are derived, respectively, indicating that at least the adsorption force of 30 N and the motor torque of 2 N·m are required for stable climbing of the robot. Furthermore, the prototype of the wall-climbing robot is manufactured and the climbing abilities are tested on various wall surfaces showing that the maximum moving speed and corresponding load are 7.11 cm/s and 0.8 kg on the concrete exterior wall, 5.9 cm/s and 0.75 kg on the ceramic brick wall, 6.09 cm/s and 0.85 kg on the lime wall, and 5.9 cm/s and 1 kg on the acrylic surface, respectively, which demonstrates that the robot has high stability and adaptability.